Assessing the prospective impact of Brexit on the global architecture of power. A multidimensional approach focusing on UK and EU - Aursulesei, Tudor-Mugurel; Maha, Liviu-George; Topliceanu, Stefan-Catalin; Viorica, Elena-Daniela (Journal of Business Economics and Management, 2024)
Brexit has undeniably had effects on power relations in the world economy and beyond. This article aims to measure the dimensions of power for the European Union, the United States and the BRICS countries and to provide a case study about the prospective impact of Brexit on the EU’s and the UK’s positions within the global architecture of power. In this regard, the paper proposes a new method of measurement of the world power by using six dimensions of power, using data before the Brexit procedures started. The highlights of the empirical findings are that the exclusion of the UK has strengthened EU’s position only for the economic dimension of power, while for the UK, the most dominant repositioning within the power architecture due to the Brexit is recorded for the political & governance. The findings can contribute to raising awareness among policy–makers, companies, institutions and the population, both at European and at national level, about populist tendencies and attitudes towards potential separations of some member countries from the European community and their consequences for the European development from multiple perspectives.